AL ZARNUJI AND INSTRUCTIONAL IMPACT - Mujahidin Farid (International Conference on Social and Islamic Studies, 2021)
Al Zarnuji offers an educational concept that concentrates on learning by doing. Like thetimes, Islamic education in particular is also more flexible. No longer using traditionalmethods alone. In addition, he taught that education is not just a transfer of knowledgeand skills, but the most important thing is the transfer of moral values. The moral valuestaught are moral values, both physical and spiritual. This article describes how the conceptof Al Zarnuji's education has an impact on the learning process at school. This article waswritten using a qualitative approach with a case study type. Al Zarnuji's educationalconcept has an impact on the development of 3 character values in the school curriculum.The discussion ended with the recommendation of teachers in Islamic educationalinstitutions to dig deeper into Al Zarnuji's thoughts to be implemented in the learningprocess.